2020
DOI: 10.1016/j.immuni.2020.06.023
|View full text |Cite
|
Sign up to set email alerts
|

The Cytokine TGF-β Induces Interleukin-31 Expression from Dermal Dendritic Cells to Activate Sensory Neurons and Stimulate Wound Itching

Abstract: Summary Cutaneous wound healing is associated with the unpleasant sensation of itching. Here we investigated the mechanisms underlying this type of itch, focusing on the contribution of soluble factors released during healing. We found high amounts of interleukin 31 (IL-31) in skin wound tissue during the peak of itch responses. Il31 −/− mice lacked wound-induced itch responses. IL-31 was released by dermal conventional type 2 dendritic cells (cDC2s) recruited to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
61
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(61 citation statements)
references
References 60 publications
0
61
0
Order By: Relevance
“…Indeed, stimulation of airway epithelial cells with IL-31 induced an increased production of MCP1 and IL-6 cytokines known to play a role in the development of pulmonary fibrosis ( 46 ). Recent studies have revealed that the expression of IL-31 was dependent of TGF-β1 signaling in different cell types and disease conditions including fibrosis and skin wound healing ( 22 , 47 , 48 ). However, TGF- β1 independent pathways might also regulate the expression of IL-31 on CD4+ T cells.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, stimulation of airway epithelial cells with IL-31 induced an increased production of MCP1 and IL-6 cytokines known to play a role in the development of pulmonary fibrosis ( 46 ). Recent studies have revealed that the expression of IL-31 was dependent of TGF-β1 signaling in different cell types and disease conditions including fibrosis and skin wound healing ( 22 , 47 , 48 ). However, TGF- β1 independent pathways might also regulate the expression of IL-31 on CD4+ T cells.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, CLEC-2 upregulated on activated cDCs during immune challenge binds to podoplanin on LN FRCs, inhibiting contractility signaling and permitting FRC stretching and LN expansion (215). A recent paper indicates that cDCs can also communicate with sensory neurons: IL-31 released by activated dermal cDC2s in response to TGF-β produced during cutaneous wound healing acts on itch sensory neurons to potentiate the itching response of wounded mice (177).…”
Section: Revisiting Cdc Activationmentioning
confidence: 99%
“…Although CD4 1 T cells are main source of IL-31 in AD, [3][4][5][6] other cells such as dermal dendritic cells also produce IL-31 in different contexts. 20 Therefore, how IPHBA affects IL-31 production by other cells is an important issue that should be investigated in future studies.…”
Section: Resultsmentioning
confidence: 99%